An In-Silico model for evaluating the directional shock vectors in terminating and modulating rotors. (July 2022) - Kulangareth, Nikhil Valsan; Magtibay, Karl; Massé, Stéphane; Krishnakumar Nair,; Dorian, Paul; Nanthakumar, Kumaraswamy; Umapathy, Karthikeyan
Abstract: Out-of-hospital cardiac arrest (OHCA) accounts for a majority of mortality worldwide. Survivability from an OHCA highly depends on timely and effective defibrillation. Most of the OHCA cases are due to ventricular fibrillation (VF), a lethal form of cardiac arrhythmia. During VF, previous studies have shown the presence of spatiotemporally organized electrical activities called rotors and that terminating these rotor-like activities could modulate or terminate VF in an in-hospital or research setting. However, such an approach is not feasible for OHCA scenarios. In the case of an OHCA, external defibrillation remains the main therapeutic option despite the low survival rates. In this study, we evaluated whether defibrillation effectiveness in an OHCA scenario could be improved if a shock vector directly targets rotor-like, spatiotemporal electrical activities on the myocardium. Specifically, we hypothesized that the position of defibrillator pads with respect to a rotor's core axis and shock current density could influence the likelihood of rotor termination and thereby result in successful defibrillation. We created a bidomain cardiac model based on porcine heart data using Aliev–Panfilov bidomain equations. We simulated localized rotors, which we attempted to terminate using different defibrillation pad orientations relative to the rotor axis (i.e., perpendicular, parallel, and oblique). In addition, we gradually increased current densities for each defibrillation pad orientation from 4 to 12 A/m 2 . We repeated the above defibrillation procedure for rotors originating from four different locations on the ventricles. The shock parameters and the outcomes were analyzed using a Generalized Linear Mixed Model (GLMM) with Logistic Regression to link rotor termination with the defibrillation pad orientation and current density. Our results suggest the highest average likelihood of terminating rotors during VF is when defibrillator pads are placed perpendicular to the rotor axis (0.99 ± 0.03), with an average current density of 7.2 A/m 2, compared to any other orientation (parallel: 0.76 ± 0.26 and oblique: 0.08 ± 0.12). Our simulations suggest that optimal defibrillator pad orientation, combined with sufficient current density magnitude, could improve the likelihood of rotor termination during VF and thereby improving defibrillation success in OHCA patients. Graphical abstract: Highlights: Ventricular fibrillation (VF) is a highly fatal cardiac arrythmia. Defibrillation is the main therapy option for out-of-hospital cardiac arrest. Terminating spatially organized rotor-like activities might modulate or terminate VF. We optimize the defibrillation shock vector direction to terminate the rotors.